How much is worth a non-listed company?: SATA Group valuation - Borges, Maria Rouxinol Furtado de Medeiros (2017)
SATA is an airline company founded in 1941 by five Azorean friends who desired to transform the Azores in an independent archipelago and, at the same time they want to expand the Azores and the Azoreans to the World. The fact is that nowadays SATA is a group of 6 companies owning 12 aircrafts and its main business is the transportation of passengers from and to the middle of the Atlantic (Azores archipelago). Between 2013 and 2015 this company suffered some changes in their financial results, which, probably, some of the causes were due to external factors as the crises and the seasonality. However, the true/main factors that led SATA to a distress situation are related with internal management: routes, employees, fleet management and, as well, and mainly, the passengers. Aiming to understand the causes and consequences of those results, we decided to evaluate this Azorean airline through two different methods: Discounted Cash Flows (Free Cash Flows to the Firm and Free Cash Flows to the Equity) and Multiples. It is expectable that the SATA’s results will get better, however it is necessary and urgent to understand what was wrong and how the company would do to get the best possible earnings.